2020
DOI: 10.1186/s13018-020-01687-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of dorsal closing wedge calcaneal osteotomy versus posterosuperior prominence resection for the treatment of Haglund syndrome

Abstract: Background: Haglund syndrome is a common disease that causes posterior heel pain. This study compared the clinical outcomes of dorsal closing wedge calcaneal osteotomy (DCWCO) and posterosuperior prominence resection (PPR) for the treatment of Haglund syndrome. Methods: This retrospective study included 12 patients who underwent DCWCO and 32 patients who underwent PPR from January 2010 to August 2016. Patients were evaluated using the American Orthopedic Foot Ankle Society ankle-hindfoot scale (AOFAS), Victori… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 22 publications
0
33
0
Order By: Relevance
“…For open surgeries, three main approaches were used. They were the lateral approach [4,7,10,14,15,17,[19][20][21]23], medial approach [4,21,24], and midline Achilles tendon central split approach [5,17,22]. There were two studies that utilized the dorsal closing wedge osteotomy technique [7,23].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…For open surgeries, three main approaches were used. They were the lateral approach [4,7,10,14,15,17,[19][20][21]23], medial approach [4,21,24], and midline Achilles tendon central split approach [5,17,22]. There were two studies that utilized the dorsal closing wedge osteotomy technique [7,23].…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…7 Values of FPa greater than 75 degrees are suggestive of Haglund deformity. 10 At last follow-up, they evidenced a significant improvement of the AOFAS and reduction of the VAS scores, along with a normalization of the FPa within the physiological range. They concluded that percutaneous treatment for Haglund deformity is reliable and effective at approximately 17 months' follow-up.…”
Section: Discussionmentioning
confidence: 85%
“…An alternative to the above techniques that require excision of bursa, degenerative tendon, and bony prominences is a dorsal closing wedge osteotomy of the calcaneus anterior to the Haglund deformity, known as the Zadek osteotomy. [34][35][36][37] The dorsal closing wedge osteotomy relocates the insertion of the Achilles anterior and proximal and tilts the Haglund prominence away from the tendon, theoretically decreasing the friction of the tendon against the prominence. Maffulli et al 34 demonstrated on 28 patients a 100% healing rate of the osteotomy and improved outcome scores at 24 months.…”
Section: Osteotomymentioning
confidence: 99%